Pengembangan Media Audio Visual Berbantuan Canva pada Tema 7 Subtema 2 Kelas IV SDN 060857 Tembung T.A 2022/2023 - Efi Rasmasari br Sinaga; Laurensia Masri Perangin-angin; Demmu Karo-Karo; Risma Sihotang; Lala Jelita Ananda (Departement of Mathematics Education, 2024)
This research was carried out starting from the problems experienced in learning in class IV SDN 060857 Tembung, especially in the use of media in the learning process which was less creative and varied, resulting in students having difficulty understanding learning material and during learning students were less active. This study aims to produce to test the feasibility, practicality, and effectiveness of audio-visual media based on Canva. This study uses the ADDIE model which consists of analysis, design, development, implementation, and evaluation. Learning media developed through validation from questionnaire validators, material validators, media validators, and educational practitioners. The results of the feasibility study of audio-visual media based on Canva show that the media is